Dividend Payout Policy and Firm Performance: Evidence from Nigeria - Lyndon M. Etale, Peter E. Ayunku (Social Science Learning Education Journal, 2016)
This study investigated the relationship between dividend payout policy and firm performance in Nigeria, using a sample of some listed firms in the Nigerian Stock Exchange (NSE) for the period 2002 to 2012.  The study adopted comparative/descriptive research designs as a set of time series dimension of panel data estimation techniques were utilized.  The result shows a positive and significant relationship between dividend payout policy and profit after tax (PAT).  This result indicates that dividend payout policy enhances firm performance in Nigeria. While earning per share (EPS) had a negative influence on dividend payout policy of firms in Nigeria for the period the study covered.  The study therefore recommends that managers of firms should endeavor to pay dividend as dividend payout policy enhances firm performance.